THE ROLE OF REFERENCE STANDARDS IN QUALITY ASSURANCE FOR MEDICINES: REGULATORY AND METROLOGICAL ASPECTS - D. A. Leontiev; Y. V. Podpruzhnikov; N. V. Volovyk (Разработка и регистрация лекарственных средств, 2019)
Some aspects of the adequate use of reference standards (RS) for making a reliable decision on the compliance of medicines are reviewed. An analysis of the specificity of using RS with the certified value and substance/reagent, for which the nominal value is considered to be 100%, is conducted. Status and specific character of using pharmacopoeial RS are considered. Issues of the use of RS for non-pharmacopoeial test methods as well as for non-pharmacopoeial medicines, problems of provision of RS for purity tests and RS for the analysis of herbal drugs and herbal drug preparations are analyzed. Some metrological aspects of the proper use of RS related to the implementation of the concept of uncertainty and the use of the principle of insignificance are discussed.